Investigation on cation distribution and luminescence in spinel phase γ-Ga3−δO4 : Sm nanostructures using X-ray absorption spectroscopy. Issue 83 (14th November 2017) - Sharma, Aditya; Varshney, Mayora; Shin, Hyun-Joon; Chae, Keun Hwa; Won, Sung Ok
Abstract : In this study, spectroscopic investigations are employed to quantify the Ga distribution over the tetrahedral/octahedral sites and to assimilate the luminescence properties in the barely reported γ-Ga2.67 O4  : Sm nanoparticles. Abstract : In this study, spectroscopic investigations are employed to quantify the Ga distribution over the tetrahedral/octahedral sites and to assimilate the luminescence properties in the barely reported γ-Ga2.67 O4  : Sm nanoparticles. O K-edge XANES are convincing the decreased electron density in the outermost hybrid orbits of O 2p and Ga 4p, and the movement of p electrons to the inner hybrid orbits with s character under the distorted oxygen environment of γ-Ga2.67 O4  : Sm nanoparticles. The Ga K/L-edge XANES and Sm L3 /M5, 4 -edge XANES results have confirmed Ga 3+ and Sm 3+ ions, respectively, in the γ-Ga2.67 O4  : Sm nanoparticles. Quantitative determination of the cation distribution is performed by applying Ga K-edge XANES data analysis, which is further substantiated by an EXAFS data simulation, and conveys a Ga-O4 tetrahedra/Ga-O6 octahedra ratio (Ga(t)/Ga(o)) of ∼0.9, ∼1.4, ∼1.5 and ∼1.6 for the β-Ga2 O3, γ-Ga2.67 O4, γ-Ga2.67 O4  : 5Sm and γ-Ga2.67 O4  : 10Sm samples, respectively, which signify the Sm doping induced deformation of Ga-O6 octahedra via the formation of oxygen defects. Multiple luminescence centres, facilitated by the Ga-O6 octahedra distortion, O vacancies and Sm 3+ ions, have helped in a significant enhancement of the emission characteristics. Our spectroscopy investigations, with the help of XANES and EXAFS, may open new opportunities to the mechanistic understanding of metal-O polyhedra alteration induced fruition of physical/chemical properties in the less explored meta stable phases of other complex oxides.